2006
DOI: 10.1002/hep.21352
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency in patients with cirrhosis and septic shock: Effect of treatment with hydrocortisone on survival

Abstract: Relative adrenal insufficiency is frequent in patients with severe sepsis and is associated with hemodynamic instability, renal failure, and increased mortality. This study prospectively evaluated the effects of steroids on shock resolution and hospital survival in a series of 25 consecutive patients with cirrhosis and septic shock (group 1). Adrenal function was evaluated by the short corticotropin test within the first 24 hours of admission. Patients with adrenal insufficiency were treated with stress doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
207
3
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(233 citation statements)
references
References 44 publications
14
207
3
5
Order By: Relevance
“…Cardiac dysfunction in ACLF, as well as in sepsis, is related to increased TNF-a and nitric oxide, and decreased cortisol levels, 98 resulting in further vascular dilatation and decreased sensitivity to vasoconstrictors. Cortisol (see hepato-adrenal axis) is reduced in more than 50% of patients affected by chronic liver disease and concomitant sepsis, resulting in adrenal insufficiency.…”
Section: Systemic Haemodynamics and Cardiac Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac dysfunction in ACLF, as well as in sepsis, is related to increased TNF-a and nitric oxide, and decreased cortisol levels, 98 resulting in further vascular dilatation and decreased sensitivity to vasoconstrictors. Cortisol (see hepato-adrenal axis) is reduced in more than 50% of patients affected by chronic liver disease and concomitant sepsis, resulting in adrenal insufficiency.…”
Section: Systemic Haemodynamics and Cardiac Dysfunctionmentioning
confidence: 99%
“…Preliminary data indicate that administration of hydrocortisone in this setting may improve circulatory function. 98 …”
Section: Hepato-adrenal Axismentioning
confidence: 99%
“…It was suggested that .70% of patients with Child-Turcotte-Pugh grade C liver disease have some degree of hypoadrenalism (31). However, in chronic liver disease, cortisol binding protein is often reduced, lowering total serum cortisol levels and making random cortisol measurements difficult to interpret.…”
Section: Clinical Coursementioning
confidence: 99%
“…Infection, especially SBP, should be diagnosed and treated without delay. Severe sepsis associated with renal insufficiency may respond to steroids [57]; however steroid use in some populations is controversial. Refractory ascites should be treated with repeat paracentesis and intravenous albumin replacement [58] or placement of a transjugular intrahepatic portosystemic shunt if the MELD score allows it.…”
Section: Prevention and Treatmentmentioning
confidence: 99%